The Influence of the Number of Poor People, Minimum Wage, Human Development Index, and Open Unemployment Rate on Income Inequality in Yogyakarta (2010-2023) - Maghriza, Muhammad Rizqi; Hasmarini, Maulidiyah Indira (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
Income inequality refers to the disparity in income received by individuals or groups within a society, resulting in noticeable gaps. Several factors contributing to income inequality in a region include differences in economic growth, population size, and poverty levels. This study aims to analyze the direction and magnitude of the influence of factors affecting income inequality, namely the number of poor people, minimum wage, human development index, and open unemployment rate. The data used in this research is panel data from 2019 to 2023 in the Special Region of Yogyakarta. The analysis technique employed is panel data regression analysis using an econometric model (estimator). The chosen model in this study is the Random Effect Model (REM). The results indicate that income inequality in the Special Region of Yogyakarta during the 2019-2023 period is influenced by the variables of the number of poor people and the human development index. In contrast, minimum wage and open unemployment rate do not have an effect on income inequality in the region during the same period.